Conformers of valeric acid. Matrix isolation infrared spectroscopy study - Mačytė, J.; Šablinskas, V.; Čeponkus, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
Matrix isolation infrared absorption spectroscopy was combined with quantum chemical calculations to characterize valeric acid conformers. Geometries and vibrational spectra of possible valeric acid conformers were calculated using MP2 and B3LYP levels of theory. MP2 calculations predict that the most stable form of valeric acid is a nonlinear aliphatic chain conformer, this contradicts B3LYP findings. Infrared absorption spectra of valeric acid isolated in argon and neon matrices exhibit complicated band structures suggesting the presence of more than one structure of valeric acid trapped in the matrices. A comparison of calculated and experimental spectra allowed us to conclude that three conformers are trapped in argon and neon matrices. Two of them, the linear chain called here TTTT and nonlinear TGTT, are found in equal distribution while the third one GGTT is less populated, at the 1:3 ratio to the most stable one.